Peran Orangtua dalam Pendidikan Karakter Anak pada Keluarga Prasejahtera - Reiza Nuary Asih Hartono; Sri Lestari (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2023)
The pre-prosperous family is a family that is in level of less of everything so they should spent their time to fulfill their economic necessity. Meanwhile, other tasks couldn’t be touched include educational is the main duty of parents who have important role in children psychological progress. Basically, the child's character is formed and forged by the environment around them through value education, this education becomes knowledge of value. This research intends to describe parent's role of children character education at pre-posperous family using qualitative approach with a method of case studies. The informant of this research were parents (father and mother) with children in middle school (13-15 years old), had a incapable paper of pre-posperous family were about 16 informant (6 fathers , 6 mothers, and 4 children.) The subject of this research was chosen by purposive sampling. Data collection with a semi-structured interview and the validity of triangulating data sources as well as analysis techniques used by thematic analysis.The result of this research reveals that the values that are considered as important value include the value of worship, the value of responsibility, the value of well-mannered, the value of bear a hand, the value of living independently, the value of self – suffeciency, the value of respect, the value of discipline and the value of honest.The relation between parents and children concerns on parental attention, child reaction, constraints in the deliver of character values, child opennes to parent, parent's role and method in transmitting the child character values to Pre-Prosperous  family by giving an advice, setting and example, administering punishment, perfoming oversight.The child applies the character values implanted by their parents in daily activities as well as the discipline of worship, speaking with manners and respect.